Loss of monoacylglycerol O-acyltransferase 2 can be compensated for by diacylglycerol O-acyltransferases 1 and 2 resulting in a negligible influence on mammary cancer development found in a mouse model and verified in human tissues - Mei Yan; Wang Jing; Lu Jia-Bin; Lu Guan-Ming; Peng Li-Xia; Lang Yan-Hong; Zheng Li-Sheng; Huang Bi-Jun; Shi Yan-Xia; Qian Chao-Nan (Visualized Cancer Medicine, 2023)
Background: Dietary fat absorption involves the re-esterification of digested triacylglycerol in the enterocytes, it is a biological process catalyzed by monoacylglycerol O-acyltransferase 2 (MOGAT2, aka MGAT2), which is highly expressed in the small intestine. A previous study showed that the loss of the Mogat2 gene can prevent high-fat diet-induced obesity in mice. Obesity is associated with an increased risk of several types of cancer including a postmenopausal mammary tumor. Methods: We collected 147 patients with triple-negative breast adenocarcinoma to explore the relationship between MOGAT2 expression and overall patient survival. The TCGA data were also retrieved for analyzing the prognostic values of MOGAT2 mRNA level as well as the relationships between MOGAT2 and DGAT1/2 mRNA levels. We also used a Mogat2-deficient mouse mammary tumor model by crossing Mogat2-deficient mice with MMTV-PyMT mice to examine the effect of MOGAT2 on mammary tumor development. Results: In human triple-negative breast adenocarcinoma, elevated expression of MOGAT2 correlated with a poorer patient prognosis. Obesity could be induced by a relatively high-fat diet (37% of calories from fat) in the mice with or without Mogat2 knockout. Mammary tumor development was deteriorated by a relatively high-fat diet regardless of Mogat2 deficiency. As a compensation mechanism, upregulation of diacylglycerol O-acyltransferases 1 and 2 (Dgat1 and Dgat2) in the Mogat2 deficient mice was found. Consistently, in human normal tissues adjacent to breast cancer, an inverse correlation between MOGAT2 mRNA level and DGAT1/2 mRNA levels was also found. Conclusions: Elevated expression of MOGAT2 in triple-negative breast adenocarcinoma predicts poorer patient overall survival. With the compensation of Dgat1 and Dgat2, Mogat2 deficiency alone cannot prevent fat diet-induced obesity, nor prevent mammary tumor development in a mouse model.